Mutations in Profilin 1 Cause Early‐Onset Paget's Disease of Bone With Giant Cell Tumors. (10th March 2021) - Wei, Zhe; Li, Shanshan; Tao, Xiaohui; Zhu, Guoying; Sun, Zhenkui; Wei, Zhanying; Jiao, Qiong; Zhang, Huizhen; Chen, Lin; Li, Baojie; Zhang, Zhenlin; Yue, Hua
ABSTRACT: Paget's disease of bone (PDB) is a late‐onset chronic progressive bone disease characterized by abnormal activation of osteoclasts that results in bone pain, deformities, and fractures. PDB is very rare in Asia. A subset of PDB patients have early onset and can develop malignant giant cell tumors (GCTs) of the bone (PDB/GCTs), which arise within Paget bone lesions; the result is a significantly higher mortality rate. SQSTM1, TNFRSF11A, OPG, VCP, and HNRNPA2B1 have been identified as pathogenic genes of PDB, and ZNF687 is the only confirmed gene to date known to cause PDB/GCT. However, the molecular mechanism underlying PDB/GCT has not been fully elucidated. Here, we investigate an extended Chinese pedigree with eight individuals affected by early‐onset and polyostotic PDB, two of whom developed GCTs. We identified a heterozygous 4‐bp deletion in the Profilin 1 ( PFN1 ) gene (c.318_321delTGAC) by genetic linkage analysis and exome sequencing for the family. Sanger sequencing revealed another heterozygous 1‐bp deletion in PFN1 (c.324_324delG) in a sporadic early‐onset PDB/GCT patient, further proving its causative role. Interestingly, a heterozygous missense mutation of PFN1 (c.335 T > C) was identified in another PDB/GCT family, revealing that not only deletion but also missense mutations in PFN1 can cause PDB/GCT. Furthermore, we established a Pfn1 ‐mutated mouse model (C57BL/6J mice) and successfully obtained Pagetic phenotypes in heterozygous mice, verifying loss of function of PFN1 as the cause of PDB/GCT development. In conclusion, our findings reveal mutations in PFN1 as the pathological mechanism in PDB/GCT, and we successfully established Pfn1 ‐mutated mice as a suitable animal model for studying PDB‐associated pathological mechanisms. The identification of PFN1 mutations has great diagnostic value for identifying PDB individuals predisposed toward developing GCTs. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).